2021
DOI: 10.5194/bg-18-3485-2021
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal intact polar lipids in polar waters: a comparison between the Amundsen and Scotia seas

Abstract: Abstract. The West Antarctic Ice Sheet (WAIS) is one of the largest potential sources of future sea-level rise, with glaciers draining the WAIS thinning at an accelerating rate over the past 40 years. Due to complexities in calibrating palaeoceanographic proxies for the Southern Ocean, it remains difficult to assess whether similar changes have occurred earlier during the Holocene or whether there is underlying centennial- to millennial-scale forcing in oceanic variability. Archaeal lipid-based proxies, specif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…There is an emerging consensus that GDGTs predominantly reflect subsurface ocean temperatures (SOT) along the Antarctic margin (Kim et al, 2012;Etourneau et al, 2019;Liu et al, 2020). This is supported by observations of elevated archaeal abundances (and GDGTs) in warmer subsurface waters (Liu et al, 2020;Spencer-Jones et al, 2021). Archaea adapt their membrane in cold waters by adding hydroxyl groups and changing the number of rings, OH-GDGTs (Fietz et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…There is an emerging consensus that GDGTs predominantly reflect subsurface ocean temperatures (SOT) along the Antarctic margin (Kim et al, 2012;Etourneau et al, 2019;Liu et al, 2020). This is supported by observations of elevated archaeal abundances (and GDGTs) in warmer subsurface waters (Liu et al, 2020;Spencer-Jones et al, 2021). Archaea adapt their membrane in cold waters by adding hydroxyl groups and changing the number of rings, OH-GDGTs (Fietz et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…GDGT contributions from >500 m from deep water Thaumarchaeotal communities are observed in the Mediterranean and near the Portugal margin influenced by deep Mediterranean Outflow Waters (Besseling et al, 2019;Kim et al, 2015Kim et al, , 2016. For the Southern Ocean, it has been suggested that a significant amount of GDGTs from depths of >1,400 m might be reaching the underlying sediments (Spencer-Jones et al, 2021). Hence, regional studies are required to constrain the source depth of the TEX 86 signal at different locations.…”
Section: Tex 86 Recordsmentioning
confidence: 99%
“…The accuracy and precision of the temperature proxies vary, especially at the upper and lower ends of the calibrations or close to detection limits, and not all proxies are found in all settings. Many of the proxies are calibrated to mean annual surface water temperature (Table 1), but if the producers have preferred seasons or water depths, a seasonal or subsurface temperature signal may be reconstructed (D'Andrea et al, 2005(D'Andrea et al, , 2011Jaeschke et al, 2017;Tierney and Tingley, 2018;Inglis and Tierney, 2020;Theroux et al, 2020;Spencer-Jones et al, 2021). Although marine biomarkers have global calibrations (Table 1), there can also be local controls over the biomarker-temperature relationship in all aquatic settings (e.g.…”
Section: Ocean and Lake Temperature Reconstructionsmentioning
confidence: 99%